Hunting in the Negev: Insights from the Late Epipaleolithic fauna of Ramat Harif. (October 2020) - Munro, Natalie D.; Lebenzon, Roxanne; Gopher, Avi; Goring-Morris, A. Nigel
Highlights: Detailed analysis of the largest Harifian faunal assemblage identified to date. The fauna show quite intensive site use, though less so than some Mediterranean Natufian sites. The Negev was more intensively occupied in the Late Epipaleolithic than ever before Changes in water distribution likely lead to abandonment of much of Negev iii in Late Pleistocene. Abstract: The Negev Desert, an arid region of the southern Levant, was only occasionally suited for human occupation in prehistory. Archaeological sites are especially abundant in the Epipaleolithic periods, likely due to changes in the availability and distribution of water resources. We consider how hunter-gatherers adapted to this sometimes marginal region by investigating human demography, site occupation intensity and population mobility by revisiting the zooarchaeological assemblage from the Late Epipaleolithic, Harifian site of Ramat Harif (12, 650/12, 500–11, 650 cal. BP) in the Central Highlands of the Negev. A near exclusive focus on ungulate species at Ramat Harif indicates efficient hunting overall. Nevertheless, high proportions of juvenile ibex and gazelle suggest intensive hunting of these two species. The rarity of other taxa in the diet indicates that they stopped short of depressing ungulate prey. Small variation in the body-part representation and age structure of the ungulates from Ramat Harif and other Late Epipaleolithic Negev sites may be linked to seasonality and their relative proximity to ibex and gazelle territories. The Negev pattern diverges from the adjacent Mediterranean zone where local Natufian populations hunted more diverse taxa, particularly small game. This pattern undoubtedly reflects higher occupation intensity and larger human populations in the Mediterranean zone as well as lower net primary production and biodiversity in the Negev desert.